2015
DOI: 10.1111/gcb.13117
|View full text |Cite
|
Sign up to set email alerts
|

On‐farm habitat restoration counters biotic homogenization in intensively managed agriculture

Abstract: To slow the rate of global species loss, it is imperative to understand how to restore and maintain native biodiversity in agricultural landscapes. Currently, agriculture is associated with lower spatial heterogeneity and turnover in community composition (β‐diversity). While some techniques are known to enhance α‐diversity, it is unclear whether habitat restoration can re‐establish β‐diversity. Using a long‐term pollinator dataset, comprising ∼9,800 specimens collected from the intensively managed agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(108 citation statements)
references
References 78 publications
(142 reference statements)
3
104
1
Order By: Relevance
“…In agricultural areas, e.g. hedgerows of native plants boosted regional biodiversity across farmed sites in California (Morandin & Kremen ; Ponisio et al ). Maintenance or reforestation of forested parcels interspersed with agricultural parcels in tropical Costa Rica enhanced pollinator communities, exhibiting a patch effect similar to ours but with patches much larger in scale (>20 ha) (Ricketts & Lonsdorf ).…”
Section: Discussionmentioning
confidence: 99%
“…In agricultural areas, e.g. hedgerows of native plants boosted regional biodiversity across farmed sites in California (Morandin & Kremen ; Ponisio et al ). Maintenance or reforestation of forested parcels interspersed with agricultural parcels in tropical Costa Rica enhanced pollinator communities, exhibiting a patch effect similar to ours but with patches much larger in scale (>20 ha) (Ricketts & Lonsdorf ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that non-crop vegetation such as herbaceous flowering field margins can support a greater abundance and diversity of bumblebees (Carvell et al 2007;Pywell et al 2011) and other native bees (Batary et al 2010a;Hopwood 2008;Williams et al 2015). Hedgerows attract bee species that are otherwise rare in agricultural settings (Hannon and Sisk 2009) and can increase the abundance and diversity of native bees and syrphid flies , increase the phenotypic diversity of the communities (Ponisio, M'Gonigle, and Kremen 2016), and even possibly increase pollinator persistence and colonization relative to unmanaged field edges.…”
Section: Vegetation Diversity and Complexitymentioning
confidence: 99%
“…Intensive agricultural systems, in particular, appear at the nexus of many of these stressors, leading to homogenization of wild bee communities and an increased reliance on managed species for pollination services [10], even though managed bees appear less suitable for achieving high fruit sets in many systems [11]. Recent research has demonstrated that wild pollination services can be enhanced through the retention or restoration of small fragments of natural habitat situated within broader agricultural landscapes [6,7,[12][13][14]. Ponisio and colleagues [14] hypothesize that, while agricultural landscapes act as an "ecological filter" through which only a restricted group of generalist pollinator taxa can pass, diverse and mature bee habitat fragments act as refugia that not only result in greater spatial heterogeneity in bee communities, but also more robust pollination service to agriculture [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that wild pollination services can be enhanced through the retention or restoration of small fragments of natural habitat situated within broader agricultural landscapes [6,7,[12][13][14]. Ponisio and colleagues [14] hypothesize that, while agricultural landscapes act as an "ecological filter" through which only a restricted group of generalist pollinator taxa can pass, diverse and mature bee habitat fragments act as refugia that not only result in greater spatial heterogeneity in bee communities, but also more robust pollination service to agriculture [12]. As a consequence, other researchers have observed that negative effects of intensive agriculture, such as pesticide exposure, can effectively be reversed if bee habitat is retained in close proximity to agricultural fields [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation